EFEKTIFITAS APLIKASI AIR SENI SAPI TERHADAP PERTUMBUHAN STEK SULUR TANAMAN CABE JAMU (Piper retrofractum Vahl.) - Sinar Suryawati; - Sucipto; Nur Syamsiyah (Agrovigor, 2009)
This research aims to determine the type of best plants vine of the long pepper as cuttings material and to determine the effectiveness of cow urine fertilizer in improving growth of cuttings. Research conducted during the dry season 2008 in the Demangan village Bangkalan district with 20-50 m height above sea level (asl), 25-33oC temperature and soil pH 5,5-6,5. Research designed factorial, consisting of 2 factors and 3 times replications using Random Design Group. The first factor is the type of vine cuttings consisting of: soil vine cutting (S1), climbing vine cuttings (S2), fruit vine cutting (S3) and the second factor is the application of cow urine fertilizer consisting of: no cow's urine (P0) , fresh cow's urine (P1), cow urine was fermented with EM4 (P2) each with a dose of 2 ml/20 ml water / plant given every 2 weeks until the cuttings was 12 weeks after planting (MST). The observed parameters include the bud emerge, amount of leaves and leaf area of plants, amount of roots and total plant dry weight. The results showed that there are interactions between the 2 factors tested against the number of roots and total plant dry weight, leaf area parameters are influenced only byvine cuttings type while the bud emerge andamount of leaves was not influenced by either factor. Climbing vine cuttings is the best type of long pepper vine because it has the highest leaf area, amount of roots and total dry weight. Cow urine fertilizer giving positive effect on the growth of cuttings, which fermented cow urine have better effect than fresh cow urine.